Progression time of de novo metastases in relation to castration resistant prostate cancer at a tertiary care hospital in Southern Thailand - Kittaweerat, Nawaporn; Chalieopanyarwong, Virote; Attawettayanon, Worapat; Pripatnanont, Choosak; Samphantharat, Thanyalak; Bejrananda, Tanan; Tanthanuch, Monthira (Insight Urology, 2022)
Objective: Androgen deprivation therapy (ADT) is often the treatment of choice in metastatic prostate cancer patients. However, there is currently an insufficiency of biomarker-related data that can be used in order to predict how the disease would respond to ADT. In this study we evaluated the clinical response to ADT, including factors which are affecting the progression of the disease into castration-resistant prostate cancer (CRPC) in patients with de novo metastatic prostate cancer. Materials and Methods: This retrospective study incorporated patients with metastatic prostate cancer who received ADT at our center from January 2008 to December 2019. Baseline characteristics, mode of ADT, prostate-specific antigen (PSA), blood chemistry, Gleason score (GS) grade group, location, and the number of metastases were analyzed. The risk factors affecting the progression of the disease were identified. Results: Data from 125 patients were included in the study. One hundred patients (80%) were classified as suffering from high volume metastatic prostate cancer and six patients (6%) with visceral metastasis. Baseline PSA in high volume and low volume metastatic prostate cancer were defined as 500 ng/ml and 215.1 ng/ ml respectively. Eighty-one patients (64.8%) received a gonadotrophin-releasing hormone (GnRH) agonist while 42 patients (33.6%) underwent bilateral orchi- ectomy. Time to CRPC in high and low volume metastasis was 12 months and 23 months respectively. Patients with Alkaline Phosphatase (ALP) ≥350 U/L had 8.5 months to CRPC while patients with ALP <350 U/L had 15 months. High GS grade group (3-5), short time to PSA nadir (<6 months), PSA nadir level (≥ 2 ng/ ml), and serum ALP ≥350 U/L were independent factors associated with shorter time to CRPC. Conclusion: The clinical management of metastatic prostate cancer is challenging; the main aims of treatment are to prolong overall survival whilst maintaining quality of life. Patients with aggressive tumors, high volume metastasis, short time to nadir (TTN), high PSA nadir level, and high ALP level were independent factors associated with shorter time to CRPC.